A MOLECULAR DIAGNOSTIC FOR WILT DISEASES OF BANANA IN SOUTH KALIMANTAN, INDONESIA - Dewi Fitriyanti; Lyswiana Aphrodyanti (Postgraduate Program - Lambung Mangkurat University (ULM Press Academic), 2016)
Among other provinces in Indonesia, South Kalimantan used to be known as one of the most famous local suppliers of bananas, especially for Java and Bali. However, since 2006 the productivity has declined dramatically due to the disruption of plant diseases. The early, fast, accurate and precise detection of the disease is needed in order to control the disease appropriately. One of the most useful, fast and accurate diagnostics that was carried out in this research was Polymerase Chain Reaction (PCR). This molecular technique has never been carried out before to detect banana diseases in South Kalimantan. This research aimed to identify the sick banana plants taken from 13 locations in 6 (six) regencies in South Kalimantan Indonesia, representing banana planting areas: Banjarbaru City, Batola, Tanah Laut, Tapin, Hulu Sungai Selatan and Hulu Sungai Tengah regencies. The results showed that the disease of all banana plant samples was positively identified as Blood Diseased Bacteria (BDB). It was established by the electroforesis result after being viewed under UV illumination that the band was at the same position as the positive control (BDB), 317 bp.7 bp.